Fetal posterior communicating artery as a conduit for concurrent anterior and posterior circulation infarct: A case report - Mohamed Micdhadhu, Mohamed Azlam; Kho, Ko Hin; Murad, Mazeda; Looi, Irene (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
Fetal type posterior cerebral artery (FTPCA) is a variant of posterior circulation of brain, in which the distal part of posterior cerebral artery (PCA) is perfused by a branch of internal carotid artery (ICA) via fetal posterior communicating artery (fetal PCOM). In the presence of fetal PCOM, a paradoxical concurrent infarction of anterior and posterior circulation may happen. We report a 67-year-old man who presented with sudden onset right sided weakness and aphasia, with National Institutes of Health Stroke Scale (NIHSS) score of 22 and clinically diagnosed to have left total anterior circulation infarct (TACI). Subsequently, he received IV Alteplase as a standard hyperacute ischemic stroke treatment. Computed tomography angiography (CTA) of brain showed left FTPCA with prominent left fetal PCOM. Subsequent computed tomography (CT) of brain showed concurrent left middle cerebral artery (MCA) and PCA territories infarct. CTA brain is commonly done in ischemic stroke cases to assess presence of large vessel occlusions and intracranial or extracranial atherosclerotic disease. However, this case depicts its additional role in detecting anatomical variants of cerebral circulation. In terms of clinical importance, presence of multiple territories infarction portends a poorer neurological outcome.